The wild parrots of Telegraph Hill [videorecording (DVD)]. - Bittner, Mark (New Video Group, 2005)
Follow the ups and downs of a flock of wild urban parrots within the green niches of San Francisco. Along the way meet unforgettable characters like Picasso and Sophie, the inseparable parrot lovers, and Connor, the lovable outcast of the flock.